2015
DOI: 10.1186/s12986-015-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-lowering activities and carbamoyl phosphate synthetase 1 (Cps1) induction mechanism of a natural flavonoid

Abstract: ObjectiveAmmonia detoxification is essential for physiological well-being, and the urea cycle in liver plays a predominant role in ammonia disposal. Nobiletin (NOB), a natural dietary flavonoid, is known to exhibit various physiological efficacies. In the current study, we investigated a potential role of NOB in ammonia control and the underlying cellular mechanism.Materials/methodsC57BL/6 mice were fed with regular chow (RC), high-fat (HFD) or high-protein diet (HPD) and treated with either vehicle or NOB. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 70 publications
4
29
0
Order By: Relevance
“…Polymethoxylated flavones elicit diverse benefits in mice and humans, including mitigating effects against cancer, inflammation, atherosclerosis, and more recently metabolic disorders and neurodegenerative diseases (Cui et al, 2010; Evans et al, 2012; Kurowska and Manthey, 2004; Lee et al, 2013; Mulvihill et al, 2009; Nohara et al, 2015a). Polymethoxylated flavones generally show a favorable pharmacokinetic profile (Evans et al, 2012; Saigusa et al, 2011), and no discernible toxicity was observed in chronic treatment of mice in this and previous studies (Lee et al, 2013; Mulvihill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymethoxylated flavones elicit diverse benefits in mice and humans, including mitigating effects against cancer, inflammation, atherosclerosis, and more recently metabolic disorders and neurodegenerative diseases (Cui et al, 2010; Evans et al, 2012; Kurowska and Manthey, 2004; Lee et al, 2013; Mulvihill et al, 2009; Nohara et al, 2015a). Polymethoxylated flavones generally show a favorable pharmacokinetic profile (Evans et al, 2012; Saigusa et al, 2011), and no discernible toxicity was observed in chronic treatment of mice in this and previous studies (Lee et al, 2013; Mulvihill et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Polymethoxylated flavones generally show a favorable pharmacokinetic profile (Evans et al, 2012; Saigusa et al, 2011), and no discernible toxicity was observed in chronic treatment of mice in this and previous studies (Lee et al, 2013; Mulvihill et al, 2011). Our recent studies showed a role of NOB in ammonia disposal via urea cycle regulation, and transcriptional induction of the rate-limiting Cps1 gene by NOB was impaired in Clock Δ19/Δ19 mutant mice (Nohara et al, 2015a). Providing a mechanistic basis for these functional results, the current study illustrates a direct role of NOB in the enhancement of circadian clocks and particularly the activation of ROR receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, N‐carbamoyl‐L‐glutamate (NCG), an allosteric activator of CPS1, has been tested to decrease ureagenesis in minority patients with CPS1D . A recent study also indicates flavonoids can rescue CPS1 levels and reduce serum ammonia in CPS1 ‐repressed mouse models . Moreover, with the genome‐editing strategies become gradually mature, for instance, CRISPR/Cas9 system, gene therapy will be a potential approach to correct CPS1 mutations in patients with CPS1D …”
Section: Discussionmentioning
confidence: 99%
“…25 A recent study also indicates flavonoids can rescue CPS1 levels and reduce serum ammonia in CPS1-repressed mouse models. 26 Moreover, with the genomeediting strategies become gradually mature, for instance, CRISPR/ Cas9 system, gene therapy will be a potential approach to correct CPS1 mutations in patients with CPS1D. 24 In conclusion, CPS1D is a rare monogenic inheritance disorder that affected multiple organs originally owing to different extent of destruction in urea cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids such as nobiletin 19 , naringin 20 , chrysin 21 , and fisetin 22,23 have been shown to improve ammonia resistance and up-regulate urea cycle enzymes 19,20,22 ; however, whether this up-regulation is effective for lowering exercise-induced hyperammonaemia remains unknown. One group of flavonoids, the green tea catechins (GTCs), have been shown to have several health-promoting impacts, including anti-cancer effects, hepatoprotective effects, anti-diabetic effects, and anti-obesity effects 24 ; however, the impact of GTCs on ammonia metabolism remains to be examined.…”
mentioning
confidence: 99%